The legality of operating short term rental accommodation in waqf housing - Daud, Mahyuddin; Mat Isa, Norlaili (2020)
Short term rental accommodation (STRA) has become more popular, especially when online hosting sites such as Airbnb have been introduced. STRA's critical popularity factor was based on the home-sharing economy. With the shared economy being a larger segment of the housing market, the discern conventional ways between activities to be regulated and activities that need to deal with without regulatory leniency. As there lacks regulation over short term rental accommodation business in Malaysia due to the technological convergence of platform operators has created an uneven playing field that threatens the position of conventional hotels in the market. The presence of STRA has also had unprecedented impacts on the Malaysian housing landscape due to the thrust of this business, including waqf housing. This paper proposed for the development of Waqf housing as the solution to balance the growth of the community and individual economy. Despite the unregulated STRA and issues surroundings, the STRA has become an alternative for an individual to leverage for income and financial. This paper examines the concept and scope of short-term rental accommodation and analyse the legal issues arising from the operationalise short term rental accommodation in waqf housing. The research presents the inadequacies in the present legislation and suggests relevant policies to address them.